2013
DOI: 10.5588/ijtld.12.0273
|View full text |Cite
|
Sign up to set email alerts
|

Toxocariasis as a cause of new pulmonary infiltrates

Abstract: Transient and migratory pulmonary infiltrates on chest CT scans were associated with blood eosinophilia and Toxocara seropositivity. Clinicians should consider asymptomatic toxocariasis as a cause of unexplained new pulmonary infiltrates in countries with dietary habits of raw meat intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…When the serum antibody positive rate was analyzed in detail by area, the correlation between eosinophil counts and antibody positivity was not significant in Seoul ( P =0.698) but significant in Gyeongsangnam-do ( P =0.014). The correlation has been consistently confirmed by several studies ( 10 , 11 , 12 , 23 , 24 , 25 , 26 , 27 ). The insignificant correlation in Seoul might have been caused by small number of antibody positive subjects in each group.…”
Section: Discussionsupporting
confidence: 74%
“…When the serum antibody positive rate was analyzed in detail by area, the correlation between eosinophil counts and antibody positivity was not significant in Seoul ( P =0.698) but significant in Gyeongsangnam-do ( P =0.014). The correlation has been consistently confirmed by several studies ( 10 , 11 , 12 , 23 , 24 , 25 , 26 , 27 ). The insignificant correlation in Seoul might have been caused by small number of antibody positive subjects in each group.…”
Section: Discussionsupporting
confidence: 74%
“…Such findings are associated with several pulmonary processes. Regarding inflammatory diseases, a pulmonary nodule with a halo is occasionally seen in patients with eosinophilic lung diseases such as simple pulmonary eosinophilia, idiopathic hypereosinophilic syndrome and parasitic infections [16]. Kim et al reported that a halo of ground-glass attenuation resulted histopathologically from pulmonary infiltrations by eosinophils and other inflammatory cells; however, they did not mention the locamanifestations of larval migration in the human body.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported, most cases of pulmonary toxocariasis are asymptomatic, manifesting as transient and migratory pulmonary infiltrates [19]. In symptomatic cases, a short course of albendazole treatment (400 mg twice daily for 5 days) is recommended, and adjunctive steroid therapy produces rapid improvement in the clinical course [2].…”
Section: Discussionmentioning
confidence: 99%